Strategi dan Kendala Guru dalam Mengimplementasikan Kewarganegaraan Digital sebagai Sumber Belajar di SMKN 3 Kediri - Wiranata, Irawan Hadi; Nugroho, Dedy Ari; Yonado, Welling; Matang, Matang (Journal of Moral and Civic Education, 2024)
Developments in the field of information technology have brought various influences, especially in the form of community participation when using digital media, giving rise to the idea of digital citizenship. In the education sector, digital citizenship can be used to build the quality of education in Indonesia. For this reason, a strategy is needed to implement digital citizenship components as a learning resource. This research aims to examine PPKn teachers' strategies in implementing digital citizenship components as a learning resource at SMKN 3 Kediri. Furthermore, exploring what obstacles are faced by PPKn teachers in implementing digital citizenship in the school. The method used in this research is a qualitative case study type using observation, interview and documentation techniques. The data analysis techniques used are data reduction, data presentation and conclusions. The results of this research found that the teacher's strategy in PPKn learning implemented digital citizenship as a learning resource in the form of education about digital ethics, use of online learning resources, class discussions, project collaboration, and digital security training. The obstacles faced by Civics Teachers in implementing digital citizenship as a learning resource are limited access and infrastructure, technical readiness and digital literacy, lack of availability of relevant content, effective assessment, security and privacy. Civics teachers' strategy in implementing digital citizenship is considered good even though there are still several obstacles in its implementation. Thus, this research recommends that teachers are able to improve and choose strategies that are tailored to students' interests and motivation, several actions can be taken such as increasing access and availability of technological infrastructure, providing adequate hardware and software to students and teachers.